Endothelial-derived angiocrine factors as instructors of embryonic development - Bishop, Daniel; Schwarz, Quenten; Wiszniak, Sophie (Frontiers in Cell and Developmental Biology, 2023)
Blood vessels are well-known to play roles in organ development and repair, primarily owing to their fundamental function in delivering oxygen and nutrients to tissues to promote their growth and homeostasis. Endothelial cells however are not merely passive conduits for carrying blood. There is now evidence that endothelial cells of the vasculature actively regulate tissue-specific development, morphogenesis and organ function, as well as playing roles in disease and cancer. Angiocrine factors are growth factors, cytokines, signaling molecules or other regulators produced directly from endothelial cells to instruct a diverse range of signaling outcomes in the cellular microenvironment, and are critical mediators of the vascular control of organ function. The roles of angiocrine signaling are only beginning to be uncovered in diverse fields such as homeostasis, regeneration, organogenesis, stem-cell maintenance, cell differentiation and tumour growth. While in some cases the specific angiocrine factor involved in these processes has been identified, in many cases the molecular identity of the angiocrine factor(s) remain to be discovered, even though the importance of angiocrine signaling has been implicated. In this review, we will specifically focus on roles for endothelial-derived angiocrine signaling in instructing tissue morphogenesis and organogenesis during embryonic and perinatal development.